A new theoretical settlement model for large step-tapered hollow piles based on disturbed state concept theory. (August 2020) - Huang, Ming; Jiang, Song; Xu, Chaoshui; Xu, Dexiang
Abstract: It is in general difficult to construct piled foundations in karst area due to the lack of a stable holding layer. A new large step-tapered hollow pile (LSTHP) is used to address this issue. In this work, the load transfer model and the theoretical solution for the settlement of the new pile are presented. FLAC 3D was used to study the load transfer mechanism of LSTHP and the load transfer model was then derived based on the mechanism in combination with the theory of disturbed states concept to characterize the non-linear pile-soil interactions. In this framework, the relatively intact state is defined by a linear elastic model while the fully adjusted state is described by the Mohr-Coulomb model. The analytical solution of pile settlement is then established based on the proposed load transfer model and the equilibrium equations governing the pile-soil interactions. The solution is cross-validated using numerical simulations. It was demonstrated that the proposed load transfer model can describe correctly the non-linear load transfer mechanism at the pile-soil interface and the analytical solution is capable of assessing the settlement of LSTHP.